Kaj raste brez korenja? O kamnih s posebnimi svojstvi na SlovenskemWhat Grows Without Roots? Stones With Special Characteristics in Slovenia - Šmitek, Zmago (Studia mythologica Slavica, 2007)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The article examines stone and petrified structures of different forms and sizes, ranging from a grain of sand to large rocky formations, which have mythological, religious, healing, fertility, prophetic, protective as well as memorial, glorifying, and symbolic meanings and functions; these make them different from other, “ordinary” stones. Since the mythological core of traditional lore about stones is closely intertwined with some other areas of traditional culture such as religion, rituals, and folk medicine, for instance, they cannot be excluded from this study.